Rodent ischemic stroke models and their relevance in preclinical research - Maria Thaysen; Emil Westi; Andrew N. Clarkson; Petrine Wellendorph; Mie Kristensen (Neuroprotection)
Abstract Stroke is a leading cause of death and disability worldwide, with ischemic stroke caused by an occluded vessel accounting for the majority of cases. Current treatments are limited to recanalization, either through thrombectomy or thrombolysis. Approved pharmacological interventions to suppress stroke‐associated excitotoxicity and neuroinflammatory events, leading to brain tissue death, are still lacking. Although numerous preclinical studies have been performed, they have yet to be translated into clinically relevant interventions. First‐line preclinical in vivo studies include the use of rodent ischemic stroke models, which vary in terms of how well they replicate human stroke pathophysiology and phenotype (including the formation of blood clot, blood–brain barrier disruption, neuroinflammation, and edema generation). Thus, rodent ischemic stroke models must be carefully chosen according to the specific pharmacological intervention to be tested. In this review, we aimed to provide an overview of the five most commonly used rodent ischemic stroke models and critically assess their advantages and limitations, with a primary focus on the acute phases of stroke.